POLYMORPISM ANALYSIS OF IL17RA GENE TO THE IL17RA CONCENTRATION AND CHRONICITY DIFFERENCES IN NEFRITIS LUPUS NL PATIENTS - Mahrus Ismail; Hani Susanti; Widodo Widodo (The East Java Biological Society, 2014)
Nefritis lupus (NL) is autoimmune disease and one of serious complication from Systemic Eritematosus Lupus (LES). Clinical manifestation of NL was variated, there are hematuria microscopic asymptomatic until renal failure. In addition of clinical manifestation, the NL disorder degree also measured from histopathological grade. Although, the mechanism that mixed up with pathogenesis of NL was known, however the cytokine also play a role to the disease process. The cytokine that assumpted have a role to the inflammation is IL-17RA, the increase production of IL-17RA influenced to the in-flammation and NL chronicity degree. The aim of this study to analyzed the relationship between polymorphism of IL-17RA gene, blood IL-17RA con-centration with the NL disorder degree. These studies were used cross sectional with control case design. The sample were used 40 patients consist NL pa-tients and Lupus patient without nephritis as a control. The polymorphisms of IL-17RA gene were investigated by using PCR method and gene sequence analysis. The alterations of allele frequency of IL-17RA gene were analyzed by bioinformatics method. The bloods IL-17RA concentration were in-vestigated by ELISA method. The NL chronicity degrees were investigated by NL histopathological grade. The hypothesis were proofed by data normality test and homogeneity test, Chi-square and Odds ratio, Spearman correlation by using SPSS 17.0 for windows. The result of showed that there are sig-nificantly different between IL-17RA gene mutant genotype frequency of NL patient (NL) with the control patient with value OR 8.48. There are sig-nificantly different between G allele of IL-17RA gene of NL patient (case) with the control patient with the value OR 4.17. There are no significantly di-fferent between IL-17RA concentrations of NL patient (case) with the different chronicity value. There are positive correlation with the OR value 4.17 bet-ween IL-17RA concentrations with the chronicity value index.